Early radiological outcome of cystic benign bone lesion treated with calcium sulphate bone graft: a one-year review - Mohamed Amin, Mohamed Azril; Mohamad Hassim, Mohamad Hafiz; Sharifudin, Mohd Ariff; Goh, Kian Liang; Ab Rahman, Jamalludin; Abd. Aziz, Azian; Md Ralib @ Md Raghib, Ahmad Razali (2016)
INTRODUCTION Benign primary bone tumours are commonly treated with intralesional curettage with or without surgical adjuvants. Moderate to large size lesions may have significant volume of bony defect following the procedure, if left alone may lead to complications like pathological fracture. The use of autograft or allograft are available options but not without limitations and complications. Polymethylmetacrylate (PMMA) does not preserve bone stock and hardened cement does not share the same biomechanic properties of bone. Problem may arise in case of osteolysis, recurrence or when arthroplasty becomes necessary.